Chassis and design & roofing fabrication / Norshahrizal Nordin … [et al.] - Nordin, Norshahrizal; Ashaary, Shazali; Maslan, Ismail; Ismail, Mohd Nasir (2000)
This study is just the first step to reveal and rediscover the one most precious invention in the past. It was started when Harley and Davidson invented the first 2- wheeled engine vehicle in mid 18's using Daimler's engine. Until it became so popular now as it was the time and space savers. At that time the American was the biggest and the best selling motorbike in the world. Today Japan had become the challenger of the pioneer itself. All this was caused by the lack of R&D by the pioneer and the attitude of static engineer (fully satisfied with what they achieved) that clung to the European engineers which made them nearly incompetent with the Japanese perfectionist. This project is a first ever research and redeveloping the motorcycle in today's everyday use. Not to be critical but ideal working in today's conditions which is different from the past.